Measuring Physicians' Response to Incentives: Evidence on Hours Worked and Multitasking - Bruce S. Shearer; Nibene Habib Somé; Bernard Fortin (Institute of Labor Economics (IZA), 2018)
We measure the response of physicians to monetary incentives using matched administrative and time-use data on specialists from Québec (Canada). These physicians were paid fee-for-service contracts and supplied a number of different services. Our sample covers a period during which the Québec government changed the prices paid for clinical services. We apply these data to a multitasking model of physician labour supply, measuring two distinct responses. The first is the labour-supply response of physicians to broad-based fee increases. The second is the response to changes in the relative prices of individual services. Our results confirm that physicians respond to incentives in predictable ways. The own-price substitution effects of a relative price change are both economically and statistically significant. Income effects are present, but are overridden when prices are increased for individual services. They are more prominent in the presence of broad-based fee increases. In such cases, the income effect empirically dominates the substitution effect, which leads physicians to reduce their supply of clinical services.
Keywords: I10; J22; J33; J44; 330; physician labour supply; multitasking; incentive pay